(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article examines modern pedagogical approaches to developing writing skills in teaching Turkish as a foreign language. Particular attention is given to the role of interactive teaching methods and individualized learning strategies in improving students’ written communication. The study analyzes how collaborative activities, digital tools, and learner-centered instruction contribute to the development of writing competence. The findings suggest that interactive and individualized approaches increase students’ motivation, enhance their linguistic accuracy, and support the development of coherent and structured written texts. The research also emphasizes the importance of competency-based education in language teaching, highlighting the role of methodological innovation in improving writing instruction.